Social media homicide confessions : stories of killers and their victims - Yardley, Elizabeth (Bristol : Policy Press, 2018)
The relationship between crime and social media has become an increasingly important topic. This text analyses what those involved in homicide do with social media. It investigates the practices of those involved and argues that confessions convey insights into the social and cultural context of contemporary homicide.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 10, 2018).
Keywords: Homicide -- Social aspects; Social media; True Crime; Social services & welfare, criminology